A performance-based optimization framework applied to a classical STM-designed deep beam. (July 2022) - Silveira, Marcos V.G.; Bitencourt, Luís A.G.; Das, Sreekanta
Highlights: The STM-designed deep beam performed brittle failure. The MCFT effectively predicted the concrete loss of strength on the tested specimen. The combined use of MCFT and damage theory showed good numerical predictions. The application of the proposed approach (STPBO) showed less consumption of steel. The STPBO-designed specimen showed improvements in structural performance. Abstract: The outcomes of experimental and numerical investigations on the design of a classical deep beam with a large opening are presented in this paper. Two structural members were designed using the strut-and-tie method (STM) and the elastic–plastic stress fields method, respectively. In this study, a performance-based optimization framework, called strut-and-tie performance-based optimization, was developed. The method and its application are presented in this paper. The method applies a performance-based optimization process in an STM-designed structural member. The finite element method was used to measure the performance along the optimization process. A large-scale experimental test was conducted on the first specimen. The modified compression-field theory (MCFT) and the digital image correlation technique were used to investigate the failures of the tested specimen. In addition, a numerical simulation strategy that combines damage theory with MCFT was used. The numerical results showed good agreement with the experimental results of the STM-designed specimen. Finally, the same numerical approach was utilized to predict the behavior of the other two members. Comparisons in terms of the use of materials and structural performance demonstrated that the proposed method for the design of deep beams is promising.